Barriers to technology integration in Indonesian language learning in Solo Raya: A TPACK framework-based analysis - Hidayah, Laila Fitri Nur; Sumarwati, Sumarwati; Anindyarini, Atikah; Mulyono, Slamet; Suryanto, Edy (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
Technology integration in Indonesian language learning is a crucial requirement in the transformation of 21st-century education, but its implementation at the classroom level still faces various obstacles. This study aims to analyze the obstacles to technology integration in Indonesian language learning in the Solo Raya region using the Technological Pedagogical and Content Knowledge (TPACK) framework. This study used an evaluative research design with the CIPP (Context, Input, Process, Product) model and applied a mixed-method approach with a dominant qualitative approach. Data were collected through classroom observations, in-depth interviews with Indonesian language teachers and MGMP coordinators, questionnaire distribution, and analysis of digital learning documentation. The research subjects included Indonesian language teachers and junior high school students in the Surakarta, Karanganyar, Boyolali, and Wonogiri regions. Data were analyzed descriptively qualitatively using the interactive analysis model of Miles, Huberman, and Saldaña, with triangulation applied to maintain the validity of the findings. The results showed that obstacles to technology integration stem not only from teachers' limited technological knowledge, but also from the weak integration between technological knowledge, pedagogy, and Indonesian language learning content. Technology tends to be used instrumentally and has not been pedagogically integrated. Contextual factors such as limited infrastructure and students' digital literacy contribute to these barriers. This study concludes that effective technology integration in Indonesian language learning requires holistic and contextual strengthening of TPACK, not simply improving digital device proficiency.